PRECOMPACTION EXPOSURE OF CHONDRULES AND IMPLICATIONS - Polnau E.; Eugster O.; Burger M.; Krahenbuhl U.; Marti K. (My University, 2001)
Following the discovery of an apparent precompaction irradiation of a chondrule, we studied the isotopic abundances of noble gases He, Ne, and Ar in separated chondrule and matrix samples of eight ordinary chondrites. The chondrules show systematically larger concentrations of cosmogenic He, Ne, and with one exception, Ar when compared to the corresponding matrix samples. Different exposure times were calculated based on production rates, which take into account the abundances of relevant target elements in each chondrule and matrix sample. The 81Kr-Kr method was used for samples of Bjurbole to verify that different exposure times are not due to either a bias in production rates or to systematic losses of noble gases from matrix. This method self-corrects for variable shielding, is independent of calculated production rates, and insensitive to gas loss. The results show that differences in exposure ages are due to different precompaction exposures of chondrules, or components thereof, before final assembly of the meteorite. For the Sena chondrite we studied various chondrule and matrix constituents. For this meteorite we found chondrule preexposures relative to the matrix material, with magnetic chondrules showing the largest effect.